2015
DOI: 10.1002/2015gl063093
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic fracture energy budget: Insights from the laboratory

Abstract: In this paper we present results from a series of laboratory hydraulic fracture experiments designed to investigate various components of the energy budget. The experiments involved a cylindrical sample of Westerly granite being deformed under various triaxial stress states and fractured with distilled water, which was injected at a range of constant rates. Acoustic emission sensors were absolutely calibrated, and the radiated seismic energy was estimated. The seismic energy was found to range from 7.02E−8% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
97
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 26 publications
20
97
2
Order By: Relevance
“…Our results show that fracture energy ( W frac ) accounts for a small fraction of input energy, similar to energy budget estimations from field, laboratory observations, and numerical studies (Fulton & Rathbun, ; Goodfellow et al, ; Herbert et al, ; Pittarello et al, ). Additionally, we show that the fraction of input energy partitioned into fracture growth is a function of rock strength and confining pressure and is influenced by microscale processes.…”
Section: Discussionsupporting
confidence: 88%
“…Our results show that fracture energy ( W frac ) accounts for a small fraction of input energy, similar to energy budget estimations from field, laboratory observations, and numerical studies (Fulton & Rathbun, ; Goodfellow et al, ; Herbert et al, ; Pittarello et al, ). Additionally, we show that the fraction of input energy partitioned into fracture growth is a function of rock strength and confining pressure and is influenced by microscale processes.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, De Barros et al () found that more than 99.99% of the deformation is aseismic performing similar injection experiments in shale materials. At the laboratory scale (i.e., centimeter), Goodfellow et al () performed hydraulic fracture experiments on granite samples under different triaxial stress and investigated the energy budget. Using acoustic emission sensors, they estimated that the seismic energy represented 4 to 8% of the injection energy, indicating that aseismic deformation is a significant term in the total energy budget.…”
Section: Discussionmentioning
confidence: 99%
“…The dotted line represents the theoretical prediction from McGarr (). Data are from Buijze et al (), De Barros et al (), Goodfellow et al (), Maxwell (), McGarr (), and this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent laboratory studies have shown that there is significant similarity between the lab and field scales on key seismic parameters; for example, Yoshimitsu et al () found that the physical processes at these scales were highly similar in that the seismic moment is inversely proportional to the cube of the corner frequency. Among hydraulic fracture experiments, Goodfellow et al () suggest that the seismic energy radiated as a proportion of the injection energy during HF scales is consistent between the laboratory and the field scales at around 1×107% to 1×105% and that the seismic moment of the recorded microseisms are log‐proportional to the injected fluid volume across scales. The radiated seismic energy approach has since been employed by researchers such as Jestin et al () to study the seismicity of tensile fractures propagating through material interfaces, where they found that seismic efficiency increases with the square root of crack velocity.…”
Section: Introductionmentioning
confidence: 94%